Roger Caillois : searches for wholeness - Montgomery, Gerardine (Trinity College (Dublin, Ireland). Department of French, 2000)
This thesis argues that the primordial concern in Roger Caillois's oeuvre is his search for wholeness. It follows this search through Caillois's often controversial and always challenging involvement in a wide range of disciplines, from mythology to mineralogy. From the start Caillois explored and expressed an inter-disciplinary approach to knowledge, and this consistency is traced in this thesis. His personal approach to his various fields of interest is considered, and his work is set against the wider cultural and political context. Caillois’s involvement with Surrealism and the College de Sociologie is an important focus in this work. His role as stimulator of the imagination is stressed, as are the conflicts and contrasts in his writing between rationality and boldness of vision. The subjective, the lyrical had no place in his search and he would combat them in all areas, particularly the poetic.
Keywords: French Language and Literature, Ph.D.; Ph.D. Trinity College Dublin